Efektivitas Model Pembelajaran Problem Based Learning dan Problem Solving Ditinjau dari Kemampuan Pemecahan Masalah Matematika Siswa Sekolah Dasar - Sukamti, Tri; Mawardi, Mawardi (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to determine the difference in the effectiveness of Mathematics problem-solving between fifth-grade students of Gugus Dwija Wiyata Elementary School who use Problem-Based Learning (PBL) and Problem Solving (PS) learning models. The research method used is an experiment with a pretest-posttest control group design. Experimental Group 1 (PBL) consisted of 44 students, while Experimental Group 2 (PS) consisted of 43 students. Data were collected through pretests and posttests using test questions, and data analysis was performed using the t-test. The results showed a difference in effectiveness between Experimental Group 1 and Experimental Group 2, with a significance value (2-tailed) of 0.001 < 0.05. This indicates that the PBL learning model is more effective in improving Mathematics problem-solving skills compared to the PS model. Therefore, it is recommended that educators consider using the PBL learning model in Mathematics teaching at the elementary school level.